PENGARUH FAKTOR FUNDAMENTAL DALAM MEMPREDIKSI PERUBAHAN LABA - 11.42.02.0038, Ardhian Kuswidyaksono (Jurnal Mahasiswa Pasca Sarjana, 2013)
This study examined the effect of disclosure of Current Ratio (CR), Total Asset Turnover (TAT), Debt To Equity ratio (DER), and Return On Asset (ROA) To Earning. The research objective is to find empirical evidence of (a) the influence of the Current Ratio (CR) to Earning,(b) the influence of the Total Asset Turnover (TAT)to Earning, (c) the influence of the Debt To Equity ratio (DER) to Earning, (d) the influence of the Return On Asset (ROA) to Earning.The sample in this study is a manufacturing company listed in Indonesian Stock Exchange (IDX) in span of years 2009â2011. Study sample is as much as 46 companies with 138 observations. Analysis of data using multiple regression analysis to all hyphotesis.The results showed that the Current Ratio (CR) have an effect but not significan to Earning. Total Asset Turnover (TAT) have an effect but not significan to Earning, Debt To Equity ratio (DER), have a negative effect to Earning, and Return On Asset (ROA) have a significant effect to Earning. With Goodness of Fit Test showed that 48,8% Current Ratio (CR), Total Asset Turnover (TAT), Debt To Equity ratio (DER), and Return On Asset (ROA) given effect to Earning, while the rest equal to 51,8% influenced by others variable which do not check.